À propos de la traduction et de l’interprétation de Jacques 2.1 - Assaël, Jacqueline (New Testament studies, 2011)
The authors propose a new translation of James 2.1. This is based on a grammatical construction which does not force to such a degree the sense of certain expressions, and which integrates the verse in a context which insists on the vanity of eternal signs of glory. This interpretation underlines the relevance of Christology for the phrase and for the totality of the passage., French abstract: Les auteurs proposent une nouvelle traduction de Jacques 2.1. Celle-ci se fonde sur une construction grammaticale qui force moins le sens de certaines expressions et intègre le verset dans un contexte insistant sur la vanité des signes extérieurs de gloire. Cette interprétation souligne la portée christologique de la phrase et de l’ensemble du passage.